2021
DOI: 10.1128/aem.02129-20
|View full text |Cite
|
Sign up to set email alerts
|

The Symbiotic “All-Rounders”: Partnerships between Marine Animals and Chemosynthetic Nitrogen-Fixing Bacteria

Abstract: Nitrogen fixation is a widespread metabolic trait in certain types of microorganisms called diazotrophs. Bioavailable nitrogen is limited in various habitats on land and in the sea, and accordingly, a range of plant, animal, and single-celled eukaryotes have evolved symbioses with diverse diazotrophic bacteria, with enormous economic and ecological benefits. Until recently, all known nitrogen-fixing symbionts were heterotrophs such as nodulating rhizobia, or photoautotrophs such as cyanobacteria. In 2016, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 119 publications
2
3
0
Order By: Relevance
“…The coastal waters of the TEP are frequently enriched with nutrients due to seasonal upwelling, leading to nitrate levels that are roughly ten times higher than those found in seagrass beds in the Caribbean [ 31 , 32 ]. Hence, the absence of nitrogen fixation genes in the symbiont MAGs from the nitrogen-rich TEP region is consistent with the hypothesis that lucinid symbiont diazotrophy has evolved as an adaptation to life in nitrogen-poor oligotrophic habitats like tropical coral reefs and seagrass beds [ 33 ]. Although the TEP symbionts did not possess the capacity to fix nitrogen, the MAGs of all three TEP symbiont lineages encoded unique accessory metabolic capabilities that were lacking in the Caribbean symbionts.…”
Section: Discussionsupporting
confidence: 82%
“…The coastal waters of the TEP are frequently enriched with nutrients due to seasonal upwelling, leading to nitrate levels that are roughly ten times higher than those found in seagrass beds in the Caribbean [ 31 , 32 ]. Hence, the absence of nitrogen fixation genes in the symbiont MAGs from the nitrogen-rich TEP region is consistent with the hypothesis that lucinid symbiont diazotrophy has evolved as an adaptation to life in nitrogen-poor oligotrophic habitats like tropical coral reefs and seagrass beds [ 33 ]. Although the TEP symbionts did not possess the capacity to fix nitrogen, the MAGs of all three TEP symbiont lineages encoded unique accessory metabolic capabilities that were lacking in the Caribbean symbionts.…”
Section: Discussionsupporting
confidence: 82%
“…We show that our MAGs formed a monophyletic clade with those from previously described marine invertebrate animals (Figure 4). Similar to what has been reported in their symbiosis with lucinid (Petersen and Yuen, 2021). Furthermore, invertebrate colonization by Ca.…”
Section: Phylogenetic and Ecological Relationship Between Marine Inve...supporting
confidence: 86%
“…Studies of lucinid clams have shown that the Ca . Thiodiazotropha symbionts are horizontally transmitted 48 . Furthermore, invertebrate colonization by Ca .…”
Section: Discussionmentioning
confidence: 99%